Penggunaan Art Therapy untuk Mengatasi Burnout Akademik Siswa - Yakub, Elni; Mardes, Siska; Rahman, Fadhila; Dwitammi, Najwah Adyani (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
Academic Burnout is a problem experienced by students that causes a lack of motivation in learning and school activities. The high demands of school learning activities make students feel bored and physically exhausted. This occurs because the learning process has pushed students to their psychological and physical limits. Academic Burnout is a personal issue that must be addressed through the implementation of guidance and counseling services in schools. These services can be provided through individual or group counseling strategies. One group approach that is appealing to elementary school students is Art Therapy. Art Therapy is a therapeutic activity that uses the creative process as an expressive therapy for clients. This community service activity will be conducted in a two-day workshop on July 20-21, 2024, with expert faculty members as speakers. The workshop will take place from 08:00 AM to 03:00 PM WIB and will be held in Kerinci Kanan District, Siak Regency, Riau Province. The training will be guided by instructors, with participants receiving direct guidance in designing guidance and counseling services aligned with the new curriculum paradigm, enabling guidance counselors to develop skills to address students' academic Burnout using Art Therapy. The level of program goal achievement is categorized as high, at 90%. This can be seen from the participants' understanding of the stages of implementing Group Counseling with Art Therapy techniques, with teachers showing great interest in practicing the Art Therapy techniques in each session.